2020
DOI: 10.3390/app10041217
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation and Bioremediation of Pesticide-Contaminated Soil

Abstract: Management and destruction of obsolete pesticides and the remediation of pesticide-contaminated soil are significant global issues with importance in agriculture, environmental health and quality of life. Pesticide use and management have a history of problems because of insufficient knowledge of proper planning, storage, and use. This manuscript reviews recent literature with an emphasis on the management of obsolete pesticides and remediation of pesticide-contaminated soil. The rhizosphere of plants is a zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 202 publications
(286 reference statements)
1
27
0
1
Order By: Relevance
“…Phytoextraction or phytoaccumulation consists in absorbing pollutants by the root system and eventually translocate them to the aerial organs, ensuring the permanent decontamination of the site. This technique has been extensively applied to remove metals but also pesticides (Gasco et al 2019 ; Tarla et al 2020 ). Rhizofiltration is typical not only of aquatic plant species which uptake pollutants from aquatic environments but also of terrestrial plants, such as sunflower or hemp, that have an extended root system and large root surface area (Gerhardt et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoextraction or phytoaccumulation consists in absorbing pollutants by the root system and eventually translocate them to the aerial organs, ensuring the permanent decontamination of the site. This technique has been extensively applied to remove metals but also pesticides (Gasco et al 2019 ; Tarla et al 2020 ). Rhizofiltration is typical not only of aquatic plant species which uptake pollutants from aquatic environments but also of terrestrial plants, such as sunflower or hemp, that have an extended root system and large root surface area (Gerhardt et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…With this mind-set, they apply all these toxic agricultural chemicals in order to improve crop yields which they can sell and make more money. Studies carried out by some researchers (Manfo et al, 2019;Mfopou et al, 2017;Asanga-Fai et al, 2019;Tarla et al, 2013;Tarla et al, 2014;Yengoh and Ardo, 2014;Tarla et al, 2015;Nkemleke, 2019;Tarla et al, 2020;Yengoh and Ardo, 2014;Tarla et al, 2015;Nkemleke, 2019;Tarla et al, 2020) have generally shown that most of the farmers involved in market gardening, apply a lot of toxic agricultural chemicals in order to improve crop productivity and increase farm income.…”
Section: Toxic Agricultural Chemicals Used By Agroforestry and Non-agroforestry Practicing Farmersmentioning
confidence: 99%
“…Studies undertaken across Cameroon, Africa and the world have shown that toxic agricultural chemicals applied on farms, are regularly washed from crop fields into streams, lakes, rivers and oceans, polluting soils, potable water sources, and affecting aquatic life (MINADER, 2013;Abang et al, 2014;Nkemleke, 2019;Tarla et al, 2013Tarla et al, , 2015Asanga-Fai et al, 2017;Kenko et al, 2017;Tarla et al, 2020). The hazardous use of toxic agricultural chemicals on farms has attracted the attention of environmentalists, scientists and policy makers who seek to make agriculture more sustainable and environmental friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Durante la biodegradación del DDT se producen diferentes metabolitos, dependiendo de la ruta de degradación, así en la biodegradación aerobia del DDT hay deshidrocloración y el metabolito que se obtiene es el diclorodifenildicloroetileno (DDE), mientras que en la biodegradación anaerobia hay una descloración reductiva y se obtiene el diclorodifenildicloroetano (DDD) (Figura 1). Muchas de las enzimas de detoxificación y metabolismo de plaguicidas son similares en plantas y microorganismos (Van Eerd, Hoagland & Hall, 2003;Tarla et al, 2020). Se conoce que las plantas tienen la capacidad de acumular y degradar DDT.…”
Section: El Caso Particular Del Dicloro Difenil Tricloroetano (Ddt)unclassified